Effectiveness of life skills health education program: A quasi-experimental study among school students of South India - Preeti Tiwari; Poonam Ramesh Naik; Abhay Subhashrao Nirgude; Arijit Datta (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: Adolescence is a vital stage of growth and development; however, many adolescents do die prematurely due to accidents, suicide, violence, poor mental stability, depression, and other illnesses that are either preventable or treatable. Life skills are important for the promotion of well-being of adolescents and to develop positive attitude and values to lead a healthy life. OBJECTIVES: The study was conducted to assess the change in life skills postintervention and study the association between different variables and the postintervention life skills score. MATERIALS AND METHODS: A quasi-experimental study was conducted among 137 adolescents each in urban and rural schools. Life skills training module based on ten domains of life skills given by the World Health Organization was implemented using interactive teaching-learning methods. After 6 months of implementation of life skills training sessions, a postintervention assessment was done using the life skills assessment scale, and the differences in the scores were measured. RESULTS: Higher life skills score was observed postintervention, and this difference was statistically significant (P < 0.001). Higher postintervention mean score (above 15) was seen in critical thinking (19.58), self-awareness (18.03), creative thinking (15.78), and interpersonal thinking (15.15). CONCLUSION: Increase in the postintervention scores using an educational intervention module and interactive teaching-learning methods suggests effectiveness of the life skills education program. Implementing this health promotion module on life skills in the school curriculum will address the overall development of the personality of the school students.